Small schools, big ideas : the essential guide to successful school transformation - Benitez, Mara.; Davidson, Jill.; Flaxman, Laura (San Francisco, CA : Jossey-Bass, 2009)
"Developed by The Coalition of Essential Schools, one of the nation's leading school reform networks, The Essential Guide to Successful School Transformation provides a comprehensive, principle-based approach for redesigning public schools and creating new schools that enable all students to achieve at high standards. Featuring stories and examples from schools that have successfully implemented the CES model, this powerful blueprint for district and school-level administrators, teachers, reform activists, educational policy makers, and professors distills insights and wisdom gleaned from over 20 years of work restructuring public schools"--Provided by publisher.
Includes bibliographical references and index.
Keywords: School improvement programs -- United States; Coalition of Essential Schools; School improvement programs -- United States